Enhancing post-operative hypothyroidism treatment: rat thyroid autotransplantation into a pre-vascularized, retrievable cell pouch™ device - Memarnejadian, Arash; Pakshir, Pardis; Tomlinson, Madison; Berjisian, Farideh; Dortas Maffei, Ligia; Winhall, Martha; Muirhead, Ben; Mofford, Jonathan; Sheardown, Heather; Ataei Mehr, Babak; Parikh, Vijay; Shannon, Frank R.; et al. (Frontiers in Endocrinology, 2025)
IntroductionTo overcome the limitations of lifelong hormone replacement therapy for post-operative hypothyroidism, we propose autologous thyroid transplantation into the Cell Pouch™ (CP), an implantable and retrievable medical device that supports vascularization and a homeostatic environment for cell grafting. The CP is currently in clinical trials for islet transplantation in type-1 diabetes, demonstrating its capacity to support long-term graft viability. Here, we apply the CP for thyroid tissue transplantation, leveraging the natural gland’s regulatory capabilities to benefit patients unresponsive to hormone therapy. Building on previous research validating CP’s support for human thyroid grafts in a mouse model, this study evaluates its therapeutic potential in a rat model mimicking clinical thyroidectomy and autologous transplantation.MethodsWe used 24 Lewis rats to assess the CP’s safety and efficacy. After a five-week post-implantation vascularization period, thyroidectomy was performed in 15 rats, and their glands were transplanted into the CP. A non-transplant group (n=4) underwent thyroidectomy only, and a control group (n=5) received no interventions. Hormone levels (total T3, free T4, TSH) were monitored weekly for 22 weeks. Histology and scintigraphy at endpoint evaluated graft function.Results and ConclusionRats with thyroid grafts in the CP restored fT4 and T3 to baseline by weeks 4 and 7, respectively. Explantation reversed this effect. Histological analysis showed well-differentiated follicles with minimal inflammation. Scintigraphy confirmed graft viability. No adverse effects were observed in hematological, liver, or kidney parameters. These findings demonstrate that CP-enabled thyroid transplantation restores function post-thyroidectomy and is safely retrievable, with no residual thyroid tissue, marking a significant safety advancement.